Molecular Identification of Bacillus Derived from the Common Carp Intestine and Their Antibiotics Resistance - Yuniar Mulyani; Karimah Syakirotin; Kiki Haetami; Yeni Mulyani; Evi Liviawaty; Mochamad Untung Kurnia Agung (Jurnal Biodjati, 2020)
The use of bacteria as a biological control agent in aquaculture is such new hope overcoming the negative impacts of the impropriate use of antibiotics. Bacillus is widely known as a potential probiotic for aquaculture, especially which are derived from aquatic biota. Due to a concern that the role of Bacillus as a probiotic agent will be disrupted by residues of antibiotics in the water, this research aimed to identify Bacillus species from common carp intestine based on the molecular method and investigate their resistance to some com-mercial antibiotics that widely used in aquaculture. Chloramphenicol, ampicillin, and metronidazole were used to determine the Bacillus resistance to antibiotics using the Kirby Bauer method. The resistance assay was carried out with a bacterial density of 108 CFU/mL. The results showed that Bacillus isolates derived from common carp  intestine were closely related and resistant to antibiotics. Isolates that resistant to the three types of antibiotics were Cc.1.9 (CgN9) and Cc.2.18 (CgM18).